ChemInform Abstract: Aqueous Hafnium Sulfate Chemistry: Structures of Crystalline Precipitates. Issue 2 (January 2015) - Kalaji, Ali; Soderholm, L.
Abstract Crystalline precipitates resulting from the hydrolysis and subsequent condensation of HfIV aqueous acidic solutions are characterized by single crystal XRD and Raman spectroscopy.